The realm of cellulases in biorefinery development - Chandel, Anuj K.; Chandrasekhar, G.; Silva, Messias Borges; Silvério Da Silva, Silvio (Taylor & Francis, 2012)
Geopolitical concerns (unstable supply of gasoline, environmental pollution, and regular price hikes), economic, and employment concerns have been prompting researchers, entrepreneurs, and policy makers to focus on harnessing the potential of lignocellulosic feedstock for fuel ethanol production and its commercialization. The carbohydrate skeleton of plant cell walls needs to be depolymerised into simpler sugars for their application in fermentation reactions as a chief carbon source of suitable ethnologic strains for ethanol production. The role of cellulolytic enzymes in the degradation of structural carbodydrates of the plant cell wall into ready-to-fermentable sugar stream is inevitable. Cellulase synergistically acts upon plant cell wall polysaccharides to release glucose into the liquid media. Cellulase predominantly dominates all the plant cell wall degrading enzymes due to their vast and diverse range of applications. Apart from the major applications of cellulases such as in detergent formulations, textile desizing, and development of monogastric feed for ruminants, their role in biorefinery is truly remarkable. This is a major area where new research tools based upon fermentation based formulations, biochemistry, and system biology to expedite the structurefunction relationships of cellulases including cellulosomes and new designer enzymatic cocktails are required. In the last two decades, a considerable amount of research work has been performed on cellulases and their application in biomass saccharification. However, there are still technical and economic impediments to the development of an inexpensive commercial cellulase production process. Advancements in biotechnology such as screening of microorganisms, manipulation of novel cellulase encoding traits, site-specific mutagenesis, and modifications to the fermentation process could enhance the production of cellulases. Commercially, cheaper sources of carbohydrates and modified fermentation conditions could lead to more cost-effective production of cellulases with the goal to reduce the cost of ethanol production from lignocellulosics. Implementation of integrated steps like cellulase production and cellulase mediated saccharification of biomass in conjunction with the fermentation of released sugars in ethanol in a single step so called consolidated bio-processing (CBP) is very important to reduce the cost of bioethanol. This paper aims to explore and review the important findings in cellulase biotechnology and the forward path for new cutting edge opportunities in the success of biorefineries. © 2012 Informa Healthcare USA, Inc.
Keywords: Biorefinery; Cellulases; Cellulose saccharification; Fermentation; Lignocellulose